The rest is noise: on describing cognitive multiplicity. (June 2021) - Hradcová, Dana; Synek, Michal
When we describe a thing, a person or a meeting, the simple question of what belongs in the picture becomes a methodological puzzle with serious practical and ethical consequences. A descriptive account touches the contours of what is being described, fluctuating between mere description and explanation and between paranoid and reparative writing. In our textual laboratory, we describe noise as a style of music and an example of cognitive multiplicity. Two accounts – of a concert and a noisy meeting – are put besides each other to explore methods which allow us to understand noise not as an annoying otherness, but as an accessible source of multiple meanings. We suggest that reparative strategies of description, adding texture to the surface rather than uncovering the social forces beneath, broaden the field of describable experience while also enabling us to see the exclusion of people considered too noisy as a process with real effects.